Poly(ethyleneimine)‐Mediated Consecutive Hydrogenation of Carbon Dioxide to Methanol with Ru Catalysts. Issue 18 (6th May 2019) - Yoshimura, Atsuki; Watari, Ryo; Kuwata, Shigeki; Kayaki, Yoshihito
Abstract : The utilization of polymeric amines for the hydrogenation of CO2 to methanol via formamides was explored with a focus on a catalytic promoter, as well as a beneficial reaction medium with enhanced basicity. Branched and linear poly(ethyleneimine)s (PEIs) were efficiently formylated in the presence of a series of PN H P‐pincer Ru complexes under CO2 hydrogenation conditions at 100 °C in THF. The obtained N ‐formylated PEI was characterized by NMR spectroscopy. The formamide units on the polymer were reduced at a higher temperature under pressurized H2 to afford methanol and to recover the starting PEI. Moreover, PEI was optimally utilized for a one‐pot synthesis of methanol catalyzed by Ru–PN H P pincer complexes. The resulting polymer can be separated from the reaction mixture to afford methanol without the contamination of formic acid derivatives in the liquid phase. Under optimized reaction conditions of 2.0 MPa of CO2 and 6.0 MPa of H2 at 150 °C, methanol was successfully obtained with a turnover number (TON) up to 689, and the amine moiety can be used catalytically. Abstract : Poly(ethyleneimine)s are catalytically utilized for the hydrogenation of CO2 to formamide and the subsequent hydrogenolysis promoted by PN H P pincer Ru complexes. The consecutive CO2 hydrogenation produced, at maximum, three times as much methanol without contamination by amines and formic acid derivatives in the liquid phase.